Vart tog den etnologiska blicken vägen? - G. Olsson, Claes (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2011)
This article discusses ways of looking – directions, intentions and meanings. How can ways of looking cause needless suffering or show empathy and acceptance? Even gazing towards the ground to discover things being lost or thrown can raise thoughts about human conditions and the meaning of objects.